The parish chronicle and the “practical” use of pieces of work – selected examples based on an applicative example (Discourse of Law and Administration, 2021)
The author utilizes the discussion perspective and the diary of fr. Paul Peikert (an example of a parish chronicle) to present the concept elements of the directional, functional orientation of the use of works as a tool for analyzing the legal regulations concerning pieces of work. According to the author, the application of this concept allows for the separation of distinctive groups of detailed provisions concerning functional pieces and the use of a work from all the regulations of the Polish copyright law. In the author’s opinion, the application of this concept extends the basis of a more general analysis of copyright law to also include the issues important from the point of view of the function of legal provisions in relation to the value system they represent. This can be used both for theoretical activity and in the process of passing the laws and modifying the existing legal solutions. These considerations are carried out in the context of an unusual document, which was written as a “chronicle/journal” during the siege of Festung Breslau by the parish priest of St. Wawrziniec (St Lorenzo), dean and clerical counselor, Fr. Paul Peiker. The professors of the University of Wrocław – K. Jonca, A. Konieczny and J. Kosik aimed at legalizing the publication of this document.
Keywords: copyrights; piece of work; practical use of a piece of work; parish chronicle